The ways that often parted: essays in honor of Joel Marcus - Baron, Lori A.; Hicks-Keeton, Jill; Thiessen, Matthew; Marcus, Joel (Early christianity and its literature, 2018)
"This volume of essays, from an internationally renowned group of scholars, challenges popular ways of understanding how Judaism and Christianity came to be separate religions in antiquity. Essays in the volume reject the belief that there was one parting at an early point in time and contest the argument that there was no parting until a very late date. Scholars re-examine texts authored by ancient worshipers of Israel's God, resulting in a complex account of multiple partings that occurred at different places and paces in myriad ways around the ancient Mediterranean in the first four centuries CE"--